Study on runoff and soil loss in the valley and foot-hill region of Arunachal Pradesh - PATTANAAIK, SAROJ KUMAR; DEBNATH, PRANKANU (Journal of Soil and Water Conservation, 2020)
An experiment was conducted during 2013-2014 at the farm, College of Horticulture and Forestry, Central Agricultural University, Pasighat, Arunachal Pradesh for evaluating the different cropping practices in retarding runoff and soil loss under land slope varying from 2-3%. The observations were recorded for 26 number of rainfall events. The average annual rainfall of the study area is about 4510mm with erratic annual distribution. Effects of five types of cropping practice-slope treatments on conservation of runoff and soil loss were studied. The treatment T4 (maize at 3% slope) resulted in highest amount of runoff i.e. 2198.4litres and highest sediment yield of 865.8 g whereas the treatment T6 (cowpea at 3% slope) resulted in lowest runoff of 1120.5litres with lowest soil loss of 289.5 g, which are significantly different from each other. The trend of the results of soil sample nutrient analysis showed that higher content of N, P and K in lower part of the runoff plots in comparison to their middle and upper parts. This is due to the removal of nutrient from upper part to lower part of the land along with runoff water. It was found that maize-cowpea intercropping at 2:4 resulted in 38.6% less runoff and 30.7% less sediment loss.